Новые материалы по таксономии и биологии палеарктических листоверток (Lepidoptera, Tortricidae) - Будашкин, Ю.И. (Вестник зоологии, 1993)
New synonymies are established: Aelhes kasyi R a z. = A. speciosa R a z. syn. n.; A. beatricella (W I s g.) =A. ferruginea (Wlsg.), syn. n. Unknown Cochylimor-pha clathralana (S t g r.) female and A. confinis R a z. male are described, bionomic data for 17 species are given.